CERTAIN ASPECTS OF THE DIAGNOSIS OF POLYCYSTIC OVARY SYNDROME IN FERTILE WOMEN - Sattaraliyeva Hayotxon Botirali qizi (Scholar Express Journals, 2023)
Current diagnostic criteria for polycystic ovary syndrome (PCOS) are reviewed with emphasis on stratification of subtypes based on metabolic features. Then, from the identified subtype, treatment options are reviewed according to the management goal: relief of hyperandrogenemia symptoms, menstrual regulation and fertility restoration. The diagnostic features of SPCJ, including ultrasonographic features, are relevant to the diagnosis. It is believed that future studies should focus on the health outcomes of postmenopausal women with PCOS.
Keywords: Polycystic ovary syndrome; ultrasound diagnostic criteria